Late medieval popular preaching in Britain and Ireland texts, studies, and interpretations - Fletcher, Alan John 1952- (Turnhout Brepols, 2009)
This work illustrates something of the formidable and culturally constitutive force of preaching. It also examines ways in which it impinged on the production of vernacular literature and ultimately reveals the wide-spread influence of sermon discourse on contingent forms of cultural production and activity
Formerly CIP Uk. - Includes bibliographical references and index
Beitr. teilw. engl., teilw. lat.
Archivierung prüfen
Archivierung prüfen
Keywords: Preaching -- Great Britain -- History -- Middle Ages, 600-1500; Preaching -- Ireland -- History -- Middle Ages, 600-1500; Sermons, Medieval -- Great Britain -- History and criticism; Sermons, Medieval -- Ireland -- History and criticism; Preaching -- Great Britain -- History -- Middle Ages, 600-1500; Preaching -- Ireland -- History -- Middle Ages, 600-1500; Sermons, Medieval -- Great Britain -- History and criticism; Sermons, Medieval -- Ireland -- History and criticism